IMPROVING EMPLOYEE PERFORMANCE THROUGH LEADERSHIP STYLE AND WORK DISCIPLINE - Bangun, Rejeki; Siringoringo, Renniwaty; Suali, Suali; Simamora, Helprida (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Research on human resource management is highly intriguing, and employee emotional engagement can create a favorable environment for job happiness and productivity. The purpose of this study is to ascertain how leadership style and work discipline and impact employee performance. SPSS version 20 and a questionnaire for 102 respondents are used in this study. This study uses multiple linear regression techniques along with statistical analysis and quantitative research. Multiple linear regression analysis results for leadership style (X1) of 2.174 with a significance value of 0.032 and work discipline (X2) of 6.002 with a significance value of 0.000 were produced by researchers based on SPSS data analysis. The results of the simultaneous test (F test) showed a significance value of 0.000 and a score of 36.233. The conclusion of this study, the first hypothesis is that leadership style has a significant effect on employee performance, the second hypothesis is that work discipline has a significant effect on employee performance and the last hypothesis is that the two variables (leadership style, work discipline,) have a simultaneous influence on employee performance.